Extreme working hours in Western Europe and North America: A new aspect of polarization - Anna S. Burger (London School of Economics and Political Science (LSE), European Institute, 2015)
This paper analyzes the trends and root causes of extreme working hours in sixteen Western European countries, Canada, and the United States between 1970 and 2010. Earlier literature has revealed increasing trends in extreme working hours in the United States and recognized the negative repercussions of this new aspect of labor market polarization. As European average working hours have declined over the past decades, scholars have turned little attention to the analysis of extreme working hours in European countries. First, the article documents diverging patterns of extreme working hours in Western Europe. Whereas the Scandinavian and French ratios of workers with extreme hours remained very low, most other countries in Western Europe exhibit significantly higher ratios of extreme workers after the beginning of the 1990s than in the previous two decades. Second, the article detects the development of two diverging trajectories in the advanced capitalist world: one with a strong and stable labor regulation along with a balanced working hour profile and one with gradual deregulation along with an increasing ratio of long work weeks. Finally, using a series of pooled cross-section OLS estimations, the article tests five specific hypotheses, motivated by theories of the welfare state and political economy theories of globalization. The results provide strong empirical evidence for the notion that patterns of extreme working hours are not inherent in post-industrial development. The article uses data from the author's extreme working hours standardized meta-database which had been compiled from two large micro data collections: the Luxembourg Income Study database (LIS) and the Multinational Time Use Study (MTUS).
Keywords: 330; extreme working hours; working hour polarization; working hour inequality; labor regulation; welfare state